The Influence of Product Quality and Brand Image on Customer Loyality with Customer Satisfaction as Intervening Variable - Bebi Ratnasari; Ratih Juliati; Eko Handayanto (University of Muhammadiyah Malang, 2022)
This research analyzed the influence of product quality and brand image on customer loyalty with customer satisfaction at Janji Jiwa coffee shop in Blitar city. This type of research uses explanatory research, survey method and quantitive. Data were collected using questionnaires from 160 Janji Jiwa coffee shop consumers in Blitar city. The collected data was then tested using the Structural Equation Model (SEM) method in the Smart PLS 3 program application. This research found that product quality, brand image, and customer satisfaction positively and significantly affect customer loyalty. At the same time, product quality and brand image positively and significantly affect customer satisfaction. Customer satisfaction as an intervening variable can mediate the influence of product quality and brand image on customer loyalty positively and significantly.